The value of immunohistochemistry on paraffin wax embedded tissue sections in the differentiation of small lymphocytic and mantle cell lymphomas. - Singh, N (1997)
AIMS: To determine whether immunohistochemistry applied to paraffin wax embedded biopsy tissue can be used to distinguish between B-small lymphocytic lymphoma (B-SLL) and mantle cell lymphoma (MCL). METHODS: Formalin fixed, paraffin wax embedded tissue blocks of 12 cases of B-SLL and 12 cases of MCL were retrieved from the files of the Department of Pathology, Southampton University Hospitals Trust. Following antigen retrieval, where appropriate, sections were stained for CD3, CD5, CD20, CD23, CD43, Cyclin D, PGP9.5, and MIB1 using a streptavidin-biotin complex technique. RESULTS: CD20 stained the neoplastic cells of B-SLL and MCL, and CD3 labelled the reactive T cells in these tumours. In B-SLL, the T cells were generally dispersed among the tumour cells, whereas in MCL they often formed bands around tumour cell nodules. CD5 could be detected on T cells, following antigen retrieval. The level of expression on B cells of B-SLL and MCL was generally too low to allow detection in paraffin wax embedded tissues. CD23 stained B-SLL but not MCL. However, it could be detected in only five of the 12 cases of B-SLL. CD43 could be detected in most cases of B-SLL and MCL. It is not, therefore, of value in distinguishing between these tumours. It will, however, help in the differentiation of B-SLL and MCL from other low grade B cell lymphomas, such as follicle centre cell and marginal zone lymphomas. Cyclin D was expressed in all of the MCL but in none of the B-SLL. PGP9.5 showed reactivity in most cases of MCL and much weaker reactivity in B-SLL. The proliferation indexes of MCL were generally higher than those of B-SLL, as measured by MIB1 labelling. Both tumours, however, showed a wide range of values and considerable overlap. CONCLUSION: Staining for Cyclin D is the most reliable immunohistochemical mean of differentiating between B-SLL an MCL. High levels of PGP9.5, expressed in MCL, may be related to the degradation of Cyclin D by the ubiquitin pathway.